The myth of the decentralised internet - Ashwin J. Mathew (Internet Policy Review, 2016)
In popular culture, and in policy discussions, the internet is often conceived of as a decentralised technology, which cannot be controlled. Drawing from research into internet infrastructure, focusing on the Border Gateway Protocol, I show that the internet has never been, and never can be, decentralised. I argue that the internet is better viewed as being distributed, both in terms of technologies and governance arrangements. The shift in perspective, from decentralised to distributed, is essential to understand the past and present internet, and to imagine possible future internets which preserve and support the public good.
Keywords: 300; Decentralisation; Governance; Protocols; Routing